Enhancing allergenicity risk assessment for novel foods in the EU: insights from the updated EFSA guidance - requirements, knowledge gaps and research needs - Laganaro, Marcello; Pieger, Anna-Maria; Muñoz-González, Alejandra; Noriega Fernández, Estefanía; Ververis, Ermolaos; Germini, Andrea; Fernández Dumont, Antonio (Frontiers in Toxicology, 2025)
With growing interest in new protein sources, driven by market trends and European Union (EU) food policy priorities, novel proteins are entering the market. These novel foods (NFs) might have the potential of introducing new allergens into the diet. In the EU, the European Food Safety Authority (EFSA) is tasked with assessing the safety of NFs and has recently updated its scientific guidance to reflect advancements in food science and built-up experience in NF risk assessment (RA). EFSA’s allergenicity RA strategy follows a weight-of-evidence approach. Data requirements depend on whether the NF is produced from or with materials containing protein, derived from known allergenic foods (whether subject to mandatory labelling or not), or has unknown allergenic potential. For the latter, a tiered approach focused on assessing the cross-allergenicity potential is applied to single proteins, protein mixtures and whole foods. However, allergenicity RA continues to face challenges including the availability of reference standard materials and the lack of agreement on the interpretation of in silico and in vitro results, as well as lack of validated and internationally recognized methods meeting regulatory requirements. These limitations underscore the need for further research to deliver robust and fit-for-purpose RA tools to support safe food systems. This review highlights key aspects of the allergenicity RA approach presented in the updated EFSA NF scientific guidance and provides a critical overview of existing uncertainties and emerging approaches aiming at encouraging international cooperation and research to further enhance allergenicity RA.